Evaluation of Students’ Satisfaction towards Instructor using Factor Analysis - Anwar Zainuddin, Mirza; Lai Jun, Jer; Bakar, Muhamad Zulhelme; Palanisamy, Kumaresan; Md Yusof, Zahayu (Journal of Science and Mathematics Letters, 2021)
Student evaluation on instructors is used in almost every high institution throughout the world whether in university or even colleges. The objective of this paper is to examine the factors that contribute to the student's evaluation on instructors among undergraduate students at Northern University of Malaysia (UUM) by using factor analysis method. The respondents of this study were 153 undergraduate students at the School of Quantitative Science via convenience sampling and snowball sampling method. The questionnaire was distributed to the participants via Google Form regarding demographic information and evaluation of the instructor. The questionnaire evaluation of the instructor consisted of 31 questions in total and 153 responses were received. The factors were classified into dependent and independent variables to identify the significance of the variables. In this paper, the variables of Student Interest, Student-Instructor, Course Demands and Course Organization were grouped as independent factors while Instructor involvement as the dependent factor.